Adenocarcinomatous Transformation of a Retroperitoneal Teratoma Mimicking an Adrenal Incidentaloma in an Adult Female: a Case Report and Literature Review - F, Babwah; V, Kumar; M, Evans; U, Karnik; A, Bhatnagar; A, Garnham; H, Buch (Archives of Clinical and Medical Case Reports, 2019)
Retroperitoneal teratomas are extremely rare in adults and are typically benign tumors. We describe a case of a 48-year-old lady who initially presented with abdominal discomfort 18 years ago and was found to have a large right-sided supra-renal mass suspected to be an adrenal lesion. Following initial biochemical and imaging studies a diagnosis of non-functioning adrenal adenoma was made and she was managed conservatively. After being lost to follow up and remaining clinically well for many years, she once again presented with worsening abdominal pain. A right adrenalectomy was performed and the histology surprisingly confirmed a mature cystic teratoma with malignant transformation into a moderately-differentiated intestinal-type adenocarcinoma as well as having a focus of carcinoid tumour. She was admitted shortly afterwards with widespread metastatic disease and sadly passed away before any treatment could be instituted. Only a handful of cases of primary retroperitoneal teratomas have described adenocarcinomatous transformation. A carcinoid tumour within a teratoma is even less common and typically does not manifest systemic features. This case underlines the broad differential diagnosis of an adrenal mass and highlights several unusual aspects of a teratoma. We present the current literature and discuss the appropriate investigations, management and challenges involved in such rare cases.